Fostering Collaboration and Enhancing Student Learning Achievement through the Integration of Ethnoscience in the Common Knowledge Construction Model with Podcast Media - Ira Fatihatussa’adah; Sri Yamtinah; Sri Retno Dwi Ariani; Antuni Wiyarsi; Hayuni Retno Widarti; Ari Syahidul Shidiq; Fadhlan Muchlas Abrori (Universitas Muhammadiyah Surakarta, 2024)
This study specifically investigates the impact of an ethnoscience-based Common Knowledge Construction Model (CKCM) learning approach integrated with podcast media on student learning outcomes and collaboration skills, concentrating on chemical bonding. The quasi-experiment research method was conducted in one of the private schools in Sukoharjo Central Java, involving 24 students in control and experimental classes. This research responds to skill demands in the 21st century to develop quality human resources by introducing innovations that integrate culture and technology into a learning system, focusing on enhancing students' soft skills, especially in collaboration. The results of the data analysis show that the learning model significantly influences student learning outcomes. However, the study indicates that this approach results in a slight improvement in students' collaboration abilities. Yet, further exploration and refinement may be necessary to enhance its effectiveness in fostering collaboration skills. This research contributes valuable insights for educators seeking innovative approaches to equip students with the skills needed to thrive in the contemporary education and employment landscape, such as competence, superiority, and competitiveness. Thus, the CKCM learning model has great potential to continue to be developed as a learning model that can answer the challenges of the 21st century.